RETRACTED: Influence of heat resistance on reproduction and productivity of Red Dairy Breed cows - Kosov Vitalij; Khrystenko Vera; Tresnitskiy Sergey; Tresnitskiy Anatoliy; Rudenko Andrei (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001